Accuracy and adequacy of photoprotection in pediatric systemic lupus erythematosus patients, and the effect of education on photoprotection: a prospective study - Porntipa Suebsarakam; Dara Mairiang (BMC, 2023)
Abstract Background Systemic lupus erythematosus (SLE) is a systemic autoimmune disease that is associated with multiple organ involvement and leads to significant morbidity and mortality. One of the important environmental factors that influences the exacerbation of preexisting SLE is ultraviolet (UV) radiation, so photoprotection is essential. The aims of this study were to evaluate the accuracy and adequacy of photoprotection in pediatric SLE patients, and to investigate the effect of education on photoprotection. Methods SLE patients aged ≤ 18 years who attended pediatric outpatient clinics were prospectively enrolled. The accuracy and adequacy of photoprotection were assessed by the questionnaire, and compared between baseline and the ≥ 3-month follow-up timepoint. Comprehensive written and verbal photoprotection education was provided to all patients and parents/caregivers after the first assessment. Results One hundred patients were included (mean age 13.6 ± 2.5, 92% female). At the first assessment, 79% of patients used sunscreen with a sunburn protection factor ≥ 30 (77%) and protection grade of ultraviolet A +  +  + (63%). Fifty-two percent of patients applied sunscreen every day. A minority of patients applied an adequate amount of sunscreen (32%), used water-resistant sunscreen (34%), used lip balm with sunscreen (23%) and reapplied sunscreen when sweating (13%). The most commonly missed areas when applying sunscreen were the ears and dorsum of the feet. The least often practiced sun protection behavior was wearing sunglasses. The most often reported activities during the peak UV index, were playing with friends and walking to the cafeterias. At the second assessment, the majority of photoprotection practices were improved in all aspects except using water-resistant sunscreen, reapplying sunscreen when sweating, applying sunscreen on the ears and dorsum of feet, and wearing sunglasses. The main reason for not using sunscreen switched from thinking it was unnecessary at the first assessment to disliking its texture at the second assessment. Conclusions Education on photoprotection was effective in improving photoprotection practices. The photoprotection practices that need to be specifically emphasized are applying an adequate amount of sunscreen and using lip balm with sunscreen. The photoprotection which were least practiced at both the first and seconds assessments were reapplying sunscreen when sweating, applying sunscreen on the ears and dorsum of the feet, and wearing sunglasses.